2003
DOI: 10.1038/sj.leu.2402972
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of aplidin and crossresistance with other cytotoxic drugs in childhood leukemic and normal bone marrow and blood samples: a rational basis for clinical development

Abstract: To determine the potential of aplidin as a cytotoxic agent in pediatric leukemia, we tested bone marrow (BM) and peripheral blood (PB) samples (n ¼ 72) of children with different types of leukemia and healthy children in the methyl-thiazol-tetrazolium assay. Also, we compared these results with other cytotoxic drugs. Aplidin was cytotoxic in vitro at nanomolar concentrations, in a dose-dependent fashion. L-carnitine, that is applied in clinical studies to prevent myotoxicity caused by aplidin, had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Results from phase I clinical trials showed signs of clinical benefit, in terms of stabilisation of the disease, and a favourable tolerability profile, with mild and relatively infrequent side effects (Anthoney et al , 2000; Armand et al , 2001; Bowman et al , 2001; Mauroun et al , 2001; Ciruelos et al , 2002). In addition, based on recent results showing that APL presents selective cytotoxicity in vitro against childhood leukaemia cells, a phase I clinical trial to study the effect of APL in pediatric leukaemia is under implementation (Bresters et al , 2003; Erba et al , 2003). Aplidin™ is currently in phase II clinical trials for renal, head and neck, pancreas, lung (NSCLC) and colorectal cancers, and medullary thyroid carcinoma.…”
mentioning
confidence: 99%
“…Results from phase I clinical trials showed signs of clinical benefit, in terms of stabilisation of the disease, and a favourable tolerability profile, with mild and relatively infrequent side effects (Anthoney et al , 2000; Armand et al , 2001; Bowman et al , 2001; Mauroun et al , 2001; Ciruelos et al , 2002). In addition, based on recent results showing that APL presents selective cytotoxicity in vitro against childhood leukaemia cells, a phase I clinical trial to study the effect of APL in pediatric leukaemia is under implementation (Bresters et al , 2003; Erba et al , 2003). Aplidin™ is currently in phase II clinical trials for renal, head and neck, pancreas, lung (NSCLC) and colorectal cancers, and medullary thyroid carcinoma.…”
mentioning
confidence: 99%
“…Results from phase I clinical trials showed signs of clinical benefit, in terms of stabilization of the disease, and a favorable tolerability profile, with mild and relatively infrequent side effects (4 -8). Aplidin has selective cytotoxicity in vitro toward childhood leukemia cells and generally lacks cross-resistance with other known cytotoxic drugs (9,10). Aplidin is currently in phase II clinical trials in a variety of solid tumors and hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Aplidin is an extremely potent inducer of apoptosis, with concentrations that caused 50% inhibition of tumour growth (IC 50 ) in vitro in a low nanomolar range, and it also exhibits strong antitumor activity in xenograft models (Urdiales et al, 1996;Erba et al, 2002;Broggini et al, 2003;Biscardi et al, 2005). In different haematological malignancies, such as acute lymphoblastic leukaemia, acute myeloid leukaemia and lymphoma, the drug is cytotoxic on primary human cells and cell lines, even on leukaemic cells carrying cytogenetic abnormalities that have poor prognostic implications (Bresters et al, 2003;Erba et al, 2003;Gajate et al, 2003). In addition to the cytotoxic properties of Aplidin, the molecule exhibits also strong antiangiogenic activity.…”
mentioning
confidence: 99%